2021
DOI: 10.33545/pathol.2021.v4.i1c.336
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of wastage of blood components in blood bank at tertiary care hospital

Abstract: Wastage of all blood components, including RBCs, platelets (PLT), and plasma, is an important issue for hospitals worldwide. Waste is not limited to blood products and is present throughout the health care system.1 Studies of systemic waste have examined the importance of workflows in the health care environment.2 and have focused on min im iz in g operational sources of waste when issuing a variety of medications. In many of these studies, relatively simple interventions resulted in marked reductions in wasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
0
2
0
3
Order By: Relevance
“…From the perspective of donors, there is a recurring expectation that donated blood will be used to full effect and not be wasted. 93 Patients are clear that unnecessary (inappropriate) transfusions should be avoided, and initiatives pursued to address variation in practice. Other relevant PPIE initiatives include reviewing research priorities identified through the activities of two James Lind Priority Setting Partnerships, 94,95 and the 'Choosing Wisely' for blood transfusion campaign.…”
Section: N Ew Dev E Lopm E N Ts I N E Ngl a N D: Th E Btru I N Data-d...mentioning
confidence: 99%
See 1 more Smart Citation
“…From the perspective of donors, there is a recurring expectation that donated blood will be used to full effect and not be wasted. 93 Patients are clear that unnecessary (inappropriate) transfusions should be avoided, and initiatives pursued to address variation in practice. Other relevant PPIE initiatives include reviewing research priorities identified through the activities of two James Lind Priority Setting Partnerships, 94,95 and the 'Choosing Wisely' for blood transfusion campaign.…”
Section: N Ew Dev E Lopm E N Ts I N E Ngl a N D: Th E Btru I N Data-d...mentioning
confidence: 99%
“…PPIE views have driven a novel strand of transfusion research examining how differences in people's geographical location, ethnicity and socio‐economic standing may affect the care they receive. From the perspective of donors, there is a recurring expectation that donated blood will be used to full effect and not be wasted 93 . Patients are clear that unnecessary (inappropriate) transfusions should be avoided, and initiatives pursued to address variation in practice.…”
Section: New Developments In England: the Btru In Data‐driven Transfu...mentioning
confidence: 99%
“…en fazla israf edilen kan ürünlerinin trombosit süspansiyonu (%47,8), eritrosit süspansiyonu (%31) ve taze donmuş plazma (%20,3) olduğunu, Roy ve Pal en fazla israf edilen kan ürünlerinin trombosit süspansiyonu (%32,35), kriyopresipitat (%25) ve eritrosit süspansiyonu (%4,49) olduğunu tespit etmiştir. 23,27 Türkiye'de yapılan bir çalışmada, imha oranı en yüksek kan ürününün eritrosit süspansiyonu olduğu tespit edilmiştir. 7 Literatürde yaşanan bu farklılıkların, hastaların klinik durumu, hastanenin hizmet sunum kapasitesi ve ürünlerin kullanım sürelerinin farklılığına bağlı olabileceği düşünülmektedir.…”
Section: Veri̇ Anali̇zi̇unclassified
“…%47,1 olarak saptamıştır. 7,8,23,29 Hindistan, İran ve Guyana'da yürütülen araştırmalarda da benzer şekilde en önemli israf nedeninin ürünün son kullanım tarihinin dolması olduğu bulunmuştur. 4,17,25 Stanger ve ark.…”
Section: Veri̇ Anali̇zi̇unclassified
See 1 more Smart Citation